"y'+(cotx)y=xcscx\n\\newline\n\\frac{dy}{dx}+(cotx)y=(cscx)x"
This equation is a linear equation of the form
"\\frac{dy}{dx}+P(x)y=Q(x)"
To solve this equation, we multiply both sides by the integrating factor I(x):
"I(x)=e^{\\int P(x)dx}=e^{\\int cotxdx}\n\\newline\n\\int cotxdx = \\int \\frac{cosx}{sinx}dx = \\int \\frac{d(sinx)}{sinx} = ln|sinx|+c"
We take c=0. Then we get:
"I(x)=e^{ln|sinx|}=|sinx|"
Let's multiply both sides by sinx (absolute value doesn't really change anything):
"sin(x)\\frac{dy}{dx}+sinx\\cdot cotx \\cdot y=x(cscx \\cdot sinx)\n\\newline\nsinx\\frac{dy}{dx}+cosx \\cdot y=x\n\\newline\n\\frac{d}{dx}(y\\cdot sinx)=x"
Integrating both sides we get the answer:
"y\\cdot sinx=\\frac{x^2}{2}+c\n\\newline\ny=\\frac{\\frac{x^2}{2}+c}{sinx}"
Comments
Leave a comment